2018
DOI: 10.1016/j.clinph.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cortical brain integration of somatosensory afferents in ALS

Abstract: Late SEPs may provide new insights on abnormal cortical excitability affecting brain areas involved in cognitive-motor functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 126 publications
(205 reference statements)
3
3
0
Order By: Relevance
“…In addition, an initially increased SEP amplitude (enlarged N20 response) has been described in some patients, followed by a progressive reduction until its total loss, as the disease advanced to a locked-in state [ 73 ]. In line with such dynamic changes, other investigators found a decrease in sensory cortical excitability (reduction in early and late SEP cortical components: N20, P25, N30, N60, and P100), but in this study, the peripheral component of SEP (N9) was also diminished [ 74 ].…”
Section: Somatosensory Cortexsupporting
confidence: 84%
“…In addition, an initially increased SEP amplitude (enlarged N20 response) has been described in some patients, followed by a progressive reduction until its total loss, as the disease advanced to a locked-in state [ 73 ]. In line with such dynamic changes, other investigators found a decrease in sensory cortical excitability (reduction in early and late SEP cortical components: N20, P25, N30, N60, and P100), but in this study, the peripheral component of SEP (N9) was also diminished [ 74 ].…”
Section: Somatosensory Cortexsupporting
confidence: 84%
“…In addition to impaired cortical sensorimotor integration, increased response to sensory input at the spinal level may bring about a facilitatory, instead of inhibitory, response to the SAI paradigm in these patients. The same group in a more recent report also demonstrated depression of the late cortical components (N60, P100) of the median and ulnar SEPs . Because LAI activates widespread somatosensory cortical areas, such as the basal ganglia–thalamocortical loop, these late component SEP abnormalities seem compatible with our abnormal LAI findings.…”
Section: Discussionsupporting
confidence: 90%
“…The same group in a more recent report also demonstrated depression of the late cortical components (N60, P100) of the median and ulnar SEPs. 61 Because LAI activates widespread somatosensory cortical areas, such as the basal ganglia-thalamocortical loop, 30 these late component SEP abnormalities seem compatible with our abnormal LAI findings. Reduced inhibition in the SAI paradigm (P = 0.001) compared with controls was more prominent than the decreased inhibition observed in the LAI paradigm (P = 0.035) in ALS patients.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, SEP differences did not significantly progress over the 180‐day follow‐up period, thus suggesting that, although frequent at diagnosis, sensory subclinical abnormalities are usually not as rapidly progressive as motor manifestations (Theys et al, 1999). Apart from the standard SEPs, components of late SEPs (N60, P100), which reflect on cortical pathways involved in cognitive–motor functions, were significantly depressed in ALS patients (Sangari, Giron, Marrelec, Pradat, & Marchand‐Pauvert, 2018).…”
Section: Clinical Evidence Supporting the Coexistence Of Sensory Disomentioning
confidence: 99%